Pendidikan Empati: Kontribusi Pandangan Edith Stein bagi Rekonstruksi Mata Pelajaran Pendidikan Agama Katolik di Indonesia - Watratan, Elisabeth; Fatlolon, Costantinus (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
Empathy has become an integral component of the contemporary educational curriculum. This study has been formulated as a review of literature employing a critical-exposition methodology to examine Edith Stein's ideas on empathy and education, as well as her impact on Catholic Religious Education (CRE). The primary objective is to elucidate Stein's perspectives on empathy and education with the purpose of enhancing religious educational practices and fostering empathy in both educators and students within Catholic educational institutions. The fundamental inquiry of this research is: